Ultrastructure of the axonal periodic scaffold reveals a braid-like organization of actin rings - Vassilopoulos, Stéphane (Nat Commun, 2019)
Recent super-resolution microscopy studies have unveiled a periodic scaffold of actin rings regularly spaced by spectrins under the plasma membrane of axons. However, ultrastructural details are unknown, limiting a molecular and mechanistic understanding of these enigmatic structures. Here, we combine platinum-replica electron and optical super-resolution microscopy to investigate the cortical cytoskeleton of axons at the ultrastructural level. Immunogold labeling and correlative super-resolution/electron microscopy allow us to unambiguously resolve actin rings as braids made of two long, intertwined actin filaments connected by a dense mesh of aligned spectrins. This molecular arrangement contrasts with the currently assumed model of actin rings made of short, capped actin filaments. Along the proximal axon, we resolved the presence of phospho-myosin light chain and the scaffold connection with microtubules via ankyrin G. We propose that braided rings explain the observed stability of the actin-spectrin scaffold and ultimately participate in preserving the axon integrity.